How nurses support self-management of hospitalized patients through verbal communication: a qualitative study - Caroline E. M. Otter; Joost C. Keers; Celeste Reker; Jakobus Smit; Lisette Schoonhoven; Janneke M. de Man-van Ginkel (BMC, 2022)
Abstract Background Patients' self-management of the implications of their disease(s) is becoming increasingly important. Research shows that hospitalization disrupts established self-management routines. Nurses can play an important role in supporting patients' self-management. The aim of this study is to describe how nurses support the self-management of hospitalized patients through verbal communication during routine nursing care. Methods A qualitative descriptive study, using overt, non-participant observations was conducted on three wards of a general teaching hospital in the Netherlands. A total of 215 hours of nursing work during 49 shifts was observed. Data was analyzed using thematic analysis based on the six phases of Braun and Clarke. Results Our observations showed that nurses discuss patients' self-management mainly in short conversations during the care provision. Nurses ask patients about their self-management at home and stimulate patients to express their opinions and to be involved in the care process. Three themes reflect how nurses support self-management: 'Discussing patient's self-management', 'Enhancing patient's involvement in care' and 'Focusing on patient's perspective'. Conclusion Hospital nurses have methods to support hospitalized patients' self-management but it does not seem to be an integral part of daily practice. Given current developments in healthcare, it is reasonable to argue that self-management should be given greater emphasis within the hospital setting, requiring a collaborative approach with patients and other healthcare professionals across the care continuum.